2015
DOI: 10.1080/00015458.2015.11681115
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Dissection Limited to Abdominal Aorta: an Underrecognized Entity ?

Abstract: Based on our case series, IAAD remains a rare clinical condition with relative benign clinical course. Treatment was almost exclusively conservative. Recent publications state IAAD might be underrecognized and under-diagnosed compared to thoracic aortic dissections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In our literature review, 2,6,8,10,[15][16][17][18][19][20][21][22][23][24][25][26] symptomatic patients numbered 68%, and AAA or CTD coexisted in 47% and 6.4% of patients, respectively. Aortic rupture developed in 6.9% of the patients, and the iliac or visceral artery was involved in 48.4% and 11%, respectively (Table VI).…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, 2,6,8,10,[15][16][17][18][19][20][21][22][23][24][25][26] symptomatic patients numbered 68%, and AAA or CTD coexisted in 47% and 6.4% of patients, respectively. Aortic rupture developed in 6.9% of the patients, and the iliac or visceral artery was involved in 48.4% and 11%, respectively (Table VI).…”
Section: Discussionmentioning
confidence: 99%
“…Vermeersch et al reported 5 cases of asymptomatic IAAD treated conservatively with blood pressure control and strict follow-up. During the follow-up period, all patients remained symptomfree and the dissection length remained stable (7). Endovascular or surgical interventions are suggested in all patients with dissection and concomitant aortic aneurysm (aortic diameter exceeding 3 cm), or in patients with signs of aortic rupture, ischemic symptoms, and unremitting pain in a non-dilated aorta (5,6,8).…”
Section: Discussionmentioning
confidence: 99%
“…During follow up, other than two deaths before treatment and 35 deaths in the Kang et al 13 study with non-separated data, 21 deaths The overall 91% of IAADs were spontaneous, which is comparable to previous studies reporting dissection types (66.7e100%). 3,7,9,11,14,18,19,21,25,26 Hypertension, smoking, and hyperlipidaemia were the most common concomitant risk factors of IAAD, which could induce endothelial damage and a persistent inflammatory response to stimulate formation of atherosclerosis and spontaneous aortic dissection. 27,28 Therefore, all patients with IAAD should be advised on basic lifestyle interventions, including hypertension control, smoking cessation, and a decrease of salt and fat in diet.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…According to the contemporary aortic dissection guidelines, 31,32 antihypertensive and analgesic therapy are the principal components of conservative treatment, which presents an evidence-based consensus among the individual studies. 3,7,10,15e18, 26 The use of a b-blocker and vasodilator is standard antihypertensive therapy to lower systolic blood pressure. However, the pooled re-intervention rate of 18% in the conservative group was higher than the ENDO and the OS group in the present meta-analysis.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation